Local Government Strategy In Optimizing Local Tax Revenue Through The Use Of Tapping Device - Dwiani Nursasi Aprilia; Eliada Herwiyanti (SIMAK, 2023)
This research aims to describe and analyze local government strategies in anticipating potential leaks in hotel tax revenues through the use of Tapping devices as an effort to optimize regional tax revenues in Purbalingga Regency. Tapping device or tapping box in taxation refers to a tool used by tax authorities to collect tax-related data or information from individuals or entities that are obliged to pay tax. Tapping devices can be software or hardware that allows tax authorities to record financial transactions, tax payments, or other financial activities to ensure compliance with tax regulations. This research uses a qualitative approach method in the form of descriptive analysis. Primary data was obtained from information in the form of narratives or the results of interviews with the Regional Financial Agency, hotel business actors, and officers at the Tapping device management company. Secondary data in the form of realized tax revenues, data on taxpayers and tax objects as well as data related to Tapping devices were obtained from the Regional Finance Agency as the Regional Tax management agency. The results of this research show something different from several previous studies which found that the use of Tapping devices in taxation can help tax authorities in checking and monitoring tax compliance, identifying violations, and collecting taxes that should be paid. The use of Tapping devices on Hotel Tax Objects in Purbalingga Regency during the two years of implementation has not shown positive results. The use of Tapping devices has not been able to increase hotel tax revenues, in fact the average tax revenues for hotels using Tapping devices have actually decreased compared to the average tax revenues before using Tapping devices.